The civilizing process – According to Mennell, Elias and Freud: A critique. (April 2015) - Redner, Harry
This article critiques theories of the civilizing process as expounded by its leading expositors: Mennell, Elias and Freud. It begins with a criticism of Stephen Mennell's book The American Civilizing Process . This book relies on an even more famous work, Norbert Elias's The Civilizing Process . Unfortunately, Mennell's otherwise commendable attempt to capture American civilization in its historical scope and sociological complexity is misdirected because Eliasian theory is not applicable to America, as we will show, and, furthermore, offers a dubious account of civilization in general. Elias's approach is limited above all by its reliance on Sigmund Freud's doubtful speculations about civilization, as presented in Civilization and its Discontents .